2017
DOI: 10.1002/cbdv.201700121
|View full text |Cite|
|
Sign up to set email alerts
|

Highly Enantioselective Production of Chiral Secondary Alcohols with Candida zeylanoides as a New Whole Cell Biocatalyst

Abstract: The increasing demand for biocatalysts in synthesizing enantiomerically pure chiral alcohols results from the outstanding characteristics of biocatalysts in reaction, economic, and ecological issues. Herein, fifteen yeast strains belonging to three food originated yeast species Candida zeylanoides, Pichia fermentans, and Saccharomyces uvarum were tested for their capability for asymmetric reduction of acetophenone to 1-phenylethanol as biocatalysts. Of these strains, C. zeylanoides P1 showed an effective asymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Enzymes play a crucial role in green chemistry as they function as catalysts, accelerating chemical reactions without requiring harsh reaction conditions or chemicals, and are also reusable. [6][7][8][9][10][11][12][13][14] A chemo-enzymatic strategy via kinetic resolution of cis-(�)-dimethyl 1-acetylpiperidine-2,3-dicarboxylate (cis-13) has been claimed in a patent by FIS Italian Factory Synthetic SPA (Scheme 4). [15] It involves the use of covalently immobilized lipase B from Candida antarctica (CAL B).…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes play a crucial role in green chemistry as they function as catalysts, accelerating chemical reactions without requiring harsh reaction conditions or chemicals, and are also reusable. [6][7][8][9][10][11][12][13][14] A chemo-enzymatic strategy via kinetic resolution of cis-(�)-dimethyl 1-acetylpiperidine-2,3-dicarboxylate (cis-13) has been claimed in a patent by FIS Italian Factory Synthetic SPA (Scheme 4). [15] It involves the use of covalently immobilized lipase B from Candida antarctica (CAL B).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chiral secondary alcohols can be synthesized by isolated enzyme, but expensive reducing co‐enzymes, such as NADPH, and purification of enzymes are indispensable for this reaction. These disadvantages limit its use in industrial‐scale production. When compared with isolated enzymes, whole‐cell application is mostly preferred due to its cheap and effective application process as no cofactors are required as they are present in the cytoplasm unlike the purified enzymes, which require them.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral reduction is limited because of the enantioselectivity, cost of the chiral reductants and environmental issues although it is widely used in commercial production (Hodgkinson et al ., 2014). Biocatalytic reduction seems to be the most potential and competitive industrialization process compared with chemical catalysis due to its clean and ecofriendly way, mild reaction conditions and high selectivity for the substrate, which is reflected in the application of some important products (Şahin and Dertli, 2017). It is reported that the chiral compounds produced by biocatalytic reduction accounted for 20% of the total chiral alcoholic intermediates in industrial products (Honda et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%